Experimental Study on Reasonable Adsorption Time in Determination Coalbed Methane Content. (1st April 2022) - Wang, Qiao; Wang, Zhaofeng; Yue, Jiwei; Wang, Liguo; Dong, Jiaxin; Tan, Ronghui
Abstract : Accurate determination of coalbed methane (CBM) content is of great significance to coalmine methane prediction, methane extraction, and gas outburst prevention. The adsorption time affects the CBM content by affecting the Langmuir adsorption constants when using the indirect method to determine the CBM content. To determine the reasonable adsorption time, representative coal samples (anthracite, lean coal, and gas-fat coal) and different destruction types (soft coal and hard coal) were selected. The experimental methods used are mercury intrusion porosimetry test, N2 adsorption/desorption test, and methane isothermal adsorption test. The results show that the pore volume and the specific surface area obtained by the BJH method and BET model increase with increasing coal rank and destruction type. For anthracite soft and hard coal, lean soft coal, and gas-fat soft coal, the N2 adsorption/desorption hysteresis loop is not closed when the relative pressure is low, indicating the existence of ink-bottle pores in these coal samples. For all tested coal samples, the longer the adsorption time is, the larger of coal methane adsorption capacity, Langmuir constant a, and CBM content are. The Langmuir constant b decreased with increasing the adsorption time. Under the condition that the reliability of the measured value is 85%, the reasonable adsorption times of coal samples are 28 h for anthracite, 18 h for lean coal, and 9 h for gas-fat coal. This study has practical help to improve the determination of CBM content, the prediction of coal seam gas outburst, and the development of CBM.